1997
DOI: 10.1042/bj3230593
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a conserved binding motif of the dinuclear metal site in mammalian and plant purple acid phosphatases: 1H NMR studies of the di-iron derivative of the Fe(III)Zn(II) enzyme from kidney bean

Abstract: The di-iron core of mammalian purple acid phosphatases has been reproduced in the plant enzyme from kidney bean (Mr 111000) upon insertion of an Fe(II) ion in place of the native zinc(II) in the dinuclear Fe(III)Zn(II) core. The shortening of the electronic relaxation time of the metal centre allows detection of hyperfine-shifted 1H NMR resonances, although severe broadening due to Curie relaxation prevents independent signal assignment. Nevertheless, comparison of the spectral features of the structurally cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…There were at least eight paramagnetically shifted resonances in-between 110 and Ϫ30 ppm. Previous studies have shown that the T 1e of Fe(III) when part of a Fe(III)Zn(II) center is too slow to observe paramagnetically shifted 1 H resonances (48,49). Therefore, the peaks observed in Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…There were at least eight paramagnetically shifted resonances in-between 110 and Ϫ30 ppm. Previous studies have shown that the T 1e of Fe(III) when part of a Fe(III)Zn(II) center is too slow to observe paramagnetically shifted 1 H resonances (48,49). Therefore, the peaks observed in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…It has been suggested that this peak arises from a backbone NH in close proximity to the metal center (53). Although unambiguous assignments of the remaining peaks are not possible, it is likely that peaks b and c are due to either meta protons (ϪCH) on Fe(II)-bound histidines or to ␤-CH 2 protons on metal-bound histidines (49,50). Ortho protons on metal-bound histidines are usually too broad to detect (50).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…29,75 Also, 1 H NMR studies of the di-iron derivative of the red kidney bean enzyme and native mammalian enzymes provided strong evidence that the coordination environment of the chromophoric Fe(III) centers is very similar in both systems, an observation also supported by comparable charge-transfer transitions in the visible region. 76 The Fe(III) site in PAPs is coordinated to the oxygen of a deprotonated tyrosine, the nitrogen atom of a histidine, and the oxygen atoms of two aspartate residues, one of which bridges the two metal sites (Figure 4). Although no binding constants have been reported, metal ion replacement studies indicate that Fe(III) is tightly bound.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…It has been postulated that the metal ions serve to bridge an oxide that performs a nucleophilic attack, to stabilize the formation of a phosphorane intermedi-ate, and to coordinate a nucleophilic hydroxyl group to allow for deprotonation (12,13). Besides calcineurin, enzymes of the CLP superfamily also include protein serine/threonine phosphatases (14), purple acid phosphatases (15), nucleotidases, sphingomyelin phosphodiesterases (16), exonucleases, and cyclic nucleotide phosphodiesterases (11). These enzymes have broad functions but are thought to have evolved from the same ancestor (17).…”
mentioning
confidence: 99%